EFFECTIVITY OF COLD CHAIN SYSTEM IN PEELED DEVEINED TAIL ON (PDTO) COOKED PEEL VANNAMEI SHRIMP (Litopenaeus vannamei) AT PT. XYZ, EAST JAVA - Ndahawali, Daniel Heintje; Soeharso, Agusta Putri Balqis Linda; Rakhmayeni, Dyah Ayu; Wowiling, Fernando; Octikharisma, Aliffia Yusti (Politeknik Kelautan dan Perikanan Sidoarjo, 2023)
Shrimps are commodities that prone to deteriorate at room temperature. Good application on cold chain system is expected to inhibit the growth of bacteria that cause deterioration in the quality due to the unavailability of a suitable environment for bacterial activity. Tthis study aimed to determine the processing characteristics of peeled deveined tail on (PDTO) cooked peel Litopenaeus vannamei shrimp, and to identify the effectiveness of cold chain application on microbiological, organoleptic, and sensory quality at PT. XYZ, East Java, by a quantitative descriptive method with an observational approach. The results showed that the processing of PDTO Cooked Peel vannamei shrimp at PT. XYZ, East Java includes raw materials receiving, weighing I, washing I, cutting heads (de heading), washing II with a shrimp washing machine, size separation, cutting, washing III, soaking, cooking preparation, weighing II, cooking, cooling, peeling, washing IV, freezing, machine glazzing, hardening, weighing, packaging in poly bags and sealing, final checking, metal detecting I, packing in cartons, storage in cold storage, metal detecting II and loading. The cold chain of shrimp processing is applied on room, water, and shrimp raw materials effectively assessed from the results of standardized microbial, organoleptic, and sensory tests